2018
DOI: 10.1039/c8sm01085d
|View full text |Cite
|
Sign up to set email alerts
|

Salt-dependent properties of a coacervate-like, self-assembled DNA liquid

Abstract: Liquid-liquid phase separation of a polymer-rich phase from a polymer-dilute solution, known generally as coacervation, has been observed in a variety of biomolecular systems. Understanding of this process, and the properties of the resulting liquid, has been hampered in typical systems by the complexity of the components and of the intermolecular interactions. Here, we examine a single-component system comprised entirely of DNA, in which tetravalent DNA nanostar particles condense into liquids through attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(141 citation statements)
references
References 35 publications
8
132
1
Order By: Relevance
“…1B, Inset) with an activation energy Ea that is the same for all f and approximately equal to the enthalpy of hybridization of a singlenanostar overhang sequence (SI Appendix, Fig. S8), consistent with previous dynamic measurements (13,15,19). We thus interpret τc as corresponding to bond-breaking events, meaning that the high-frequency plateau modulus reflects the stiffness of an instantaneously bonded network.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…1B, Inset) with an activation energy Ea that is the same for all f and approximately equal to the enthalpy of hybridization of a singlenanostar overhang sequence (SI Appendix, Fig. S8), consistent with previous dynamic measurements (13,15,19). We thus interpret τc as corresponding to bond-breaking events, meaning that the high-frequency plateau modulus reflects the stiffness of an instantaneously bonded network.…”
Section: Resultssupporting
confidence: 84%
“…1). They found that tetravalent DNAns transition from a fluid to an equilibrium gel on cooling (16)(17)(18), with network dynamics controlled by the stickyend interaction strength (13,15,19). Equilibrium gel formation requires both limited valence (f < 12) (13,15,(20)(21)(22) and significant flexibility (16,23) as conferred by the unpaired bases in the DNAns design ( Fig.…”
mentioning
confidence: 99%
“…The viscosity and interfacial tension of the previously reported coacervate systems varied with the pH and ionic strength of the solution, the type of polyelectrolyte, the types of intermolecular attractions, the concentration of the polymers, the molecular weight and conformation of the polymers, the mixing ratio, and the temperature. However, it should be noted that the measured viscosity and interfacial tension of the protamine-citrate system were relatively low compared to previously studied coacervate systems [1,2,3,6,7,10,11,16,22,28,29,30,31].…”
Section: Resultsmentioning
confidence: 63%
“…B) Confocal fluorescence imagesofa naqueoustwo-phase system (ATPS, left) and droplets formed by complex coacervation (right). [20,29,30] These factors, together with the chemical natureso ft he speciesi nvolved (long polyelectrolytes or small molecules), influence the material properties of the coacervate phase produced, including the rheological and interfacial properties. D) Schematic phase diagramfor simple and complex coacervates, showing that phase separation occurs in cases of sufficiently stronga ttractive interactions (modulated by the ionic strength,p H, T,etc.).…”
Section: Segregative Llps:synthetic Cells Based On Aqueous Two-phase mentioning
confidence: 99%
“…Recent studies in this area have soughtt ou nderstand these factors in greaterd etail by using computational modelling combined with better-defined polyelectrolyte structures, [25] in terms of, for example, polymerl ength dispersity, [26] charge distribution, [27] chirality [28] or base pairing. [20,29,30] These factors, together with the chemical natureso ft he speciesi nvolved (long polyelectrolytes or small molecules), influence the material properties of the coacervate phase produced, including the rheological and interfacial properties. [31] The ease of coacervate formation and the diversity of assembly blocks have provided applicationsi n areas as diverse as food thickening, [32] cosmetic [33] or pharmaceutical [25b] formulations,p rotein purification, [34] wastewater treatment [35] or underwater adhesion.…”
Section: Associative Llps:c Oacervate-based Synthetic Cellsmentioning
confidence: 99%